2016
DOI: 10.1021/acs.orglett.6b02878
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of HDDA-Derived Benzynes with Perylenes: Rapid Construction of Polycyclic Aromatic Compounds

Abstract: Benzynes produced by the thermal cycloisomerization of tetrayne substrates [i.e., by the hexadehydro-Diels–Alder (HDDA) reaction] react with perylenes to produce novel naphthoperylene derivatives. Cyclic voltammetry and absorption and emission properties of these compounds are described. DFT studies shed additional light on the dearomatization that accompanies the reaction as well as some of the spectroscopic behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Nevertheless, an additional band can be observed in the longer wavelength regime (460-510 nm), which cannot be attributed to the simple 1 : 1 trapping product, but might belong to a double (2 : 1) adduct structure with extended conjugation. 47 Meanwhile, although values of the factors a and b are determined with some uncertainty, we found that alternations of a (Fig. 5e) or b (Fig.…”
Section: Intermolecular Trapping By Perylenementioning
confidence: 63%
See 2 more Smart Citations
“…Nevertheless, an additional band can be observed in the longer wavelength regime (460-510 nm), which cannot be attributed to the simple 1 : 1 trapping product, but might belong to a double (2 : 1) adduct structure with extended conjugation. 47 Meanwhile, although values of the factors a and b are determined with some uncertainty, we found that alternations of a (Fig. 5e) or b (Fig.…”
Section: Intermolecular Trapping By Perylenementioning
confidence: 63%
“…An alternative strategy for trapping o-benzyne is its reaction with species containing -C]Cbonds such as in a p-conjugated system reported recently (without time resolution). 12,15,26,47,83 We also made use of this reaction, but again employing femtosecond time-resolved techniques. The trapping product is expected to absorb in the >400 nm wavelength region where the transient absorption of the reactant bis-diynes is sufficiently weak to allow the largely unhindered observation of the trapping products.…”
Section: Intermolecular Trapping By Perylenementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent example, bay‐region APEX reactions of perylene derivatives 32 with tetraynes 31 through hexadehydro‐Diels–Alder (HDDA) reactions have been reported by Hoye and co‐workers (Scheme ) . In this reaction, simply heating induces the thermal cycloisomerization of the tetrayne to form alkynylbenzyne 34 , which then undergoes bay‐region APEX reactions to produce naphthoperylene derivatives 33 .…”
Section: Apex Reactions Of Unfunctionalized Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Carrying out the HDDA reaction in the presence of perylenes led to trapping of the intermediately formed benzynes by the Diels–Alder reaction with perylene core (Scheme ) …”
Section: Cycloaddition To Carbon–carbon Triple Bondmentioning
confidence: 99%